2015
DOI: 10.1038/nn.3972
|View full text |Cite
|
Sign up to set email alerts
|

NPY signaling inhibits extended amygdala CRF neurons to suppress binge alcohol drinking

Abstract: Summary paragraphBinge alcohol drinking is a tremendous public health problem because it leads to the development of numerous pathologies including alcohol abuse, and anxiety1–4. It is thought to do so by hijacking brain systems that regulate stress and reward, including neuropeptide Y (NPY) and corticotropin–releasing factor (CRF). The central actions of NPY and CRF play opposing functional roles in the regulation of emotional and reward–seeking behaviors; therefore, dysfunctional interactions between these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
185
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(195 citation statements)
references
References 51 publications
10
185
0
Order By: Relevance
“…For example, Pleil et al (2015) found an effect of chronic alcohol drinking on the BNST that was conserved between mice and monkeys. Importantly, recent neuroimaging studies have shown that the connectivity of the BNST in humans is in large part similar to that of rodents and non-human primates, with the addition of connections between the BNST and more rostral cortical areas such as the orbitofrontal cortex (Avery et al, 2014, Krüger et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Pleil et al (2015) found an effect of chronic alcohol drinking on the BNST that was conserved between mice and monkeys. Importantly, recent neuroimaging studies have shown that the connectivity of the BNST in humans is in large part similar to that of rodents and non-human primates, with the addition of connections between the BNST and more rostral cortical areas such as the orbitofrontal cortex (Avery et al, 2014, Krüger et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in another study chemogenetically inhibiting CRF neurons using the designer receptor exclusively activated by designer drugs (DREADD) system caused a reduction in anxiety-like behavior (Pleil et al, 2015). CRF neurons in the BNST are thought to make both local connections as well as project out of the nucleus to regions involved in emotion processing including the periventricular nucleus of the hypothalamus (PVN), ventral tegmental area (VTA), periaqueductal gray (PAG), dorsal potion of the dorsal raphe (DRD) and locus coeruleus (LC) (Dabrowska et al, 2011;Dabrowska & Rainnie, 2014;Meloni et al, 2006;Rodaros et al, 2007;Silberman et al, 2013;Van Bockstaele et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, activation of Gi/o-coupled Y1 receptors reduces NMDA receptor-mediated excitatory postsynaptic currents and increases GABA A receptormediated inhibitory postsynaptic currents by reducing the activity of exchange protein activated by cAMP (Epac) and Protein Kinase A (PKA), respectively (Molosh et al, 2013). It is worth highlighting that the Y1 receptor was also found to increase GABA A receptormediated inhibition in the BNST (Pleil et al, 2015), as this provides a fine example of the similarities in Y receptor function in different brain regions. Thus, these studies provide evidence that NPY likely exerts its potent fear-reducing effects when injected into the BLA by reducing the activity of BLA pyramidal neurons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although many studies have found that NPY typically reduces synaptic transmission, it is interesting to note that NPY can also enhance inhibitory transmission. Pleil et al (2015) demonstrated that the Y1 receptor agonist, Leu 31 Pro 34 NPY increases the frequency of miniature inhibitory postsynaptic currents in BNST neurons probably by increasing the surface expression of postsynaptic GABA A receptors (Pleil et al, 2015).…”
mentioning
confidence: 99%